The influence of personality traits on purchase intention with innovativeness as a moderating variable - Supriyanto, Andreas Reza; Kristiningsih, Kristiningsih (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
This research aims to determine the influence of self-esteem, neuroticism, agreeableness, and extraversion on purchase intention. Apart from that, it also examines the influence of innovativeness as a moderating variable on the influence of these variables. This research was conducted on electric car consumers. The sample from this research consisted of 143 respondents and was obtained using the purposive sampling method and analysis with WARP-PLS. The data collection method used was a questionnaire. The research results show that neuroticism, agreeableness, and extraversion have a significant positive effect on purchase intention. Meanwhile, self-esteem do not have a significant effect on purchase intention. The research results also found that innovativeness can moderate the influence of extraversion on purchase intention, but could not moderate the influence of self-esteem, neuroticism, and agreeableness on purchase intention.